A Study of Biomass Fuel Briquettes from Oil Palm Mill Residues - Aris, M.S.; Chin, Yee Sing (2012)
This study presents a systematic approach in utilizing the large amount of oil palm mill residues that are loosely-bounded and have low energy density. The rate of waste materials (palm kernel shell, palm fiber and empty fruit bunches) generated by oil palm mills amounted to about 34 million tonnes in 2010. Efforts have been made to increase the energy density of the loosely-bounded waste materials, in which solid fuel briquettes made of densified oil palm residues would contribute towards a more efficient utilization of the waste material. This work focused on determining a fuel briquette with an optimum ratio of waste materials mixtures that has considerably high heating value and good mechanical properties. As part of the densification process, the waste material was pulverized and then compacted using a 200 kN force into 40 mm diameter briquettes. The heating values, proximate analysis, ultimate analysis and burning profile of the briquettes were studied. The end result was an optimised solid fuel with relatively high energy content made from a suitable mixing ratio of the different palm oil mill residues and an appropriate binder to ensure acceptable mechanical strength.